The effects of adjuvant radiotherapy on survival outcomes in polymorphous adenocarcinoma: a retrospective cohort study - Matthews, Makayla R.; Fonseca, Victoria I.; Auger, Samuel; Pede, Christopher A.; Phillips, Ramez; Tasoulas, Jason; Sullivan, Christopher Blake (Translational Cancer Research, 2026)
Polymorphous adenocarcinoma (PAC) is the second most common malignant salivary tumor with a 10-year disease-specific survival (DSS) of 94%. While PAC is generally non-aggressive and surgery is often curative, some show aggressive features warranting adjuvant radiation therapy (RT). However, the impact of RT on survival outcomes remains unclear. The aim of this study is to investigate survival outcomes between patients treated with primary surgery vs. surgery with RT.